Revitalization of the Sanur Special Economic Zone (SEZ): Integrating Regional Planning, Sustainable Architecture, and Adaptive Interior Design for a Culturally-based Health Tourism Destination - I Kadek, Pranajaya; Dewi, Ni Made Emmi Nutrisia; Artayasa, I Nyoman (Journal of Regional and City Planning, 2025)
The revitalization of the Sanur Special Economic Zone (SEZ) marks a strategic shift in Indonesia’s approach to sustainable tourism development. This study examined how an integrated planning framework encompassing regional planning, green architecture, and adaptive interior design was employed to reposition Sanur as a competitive hub for health and wellness tourism. Using a case study approach, this research combined field observations, in-depth interviews with key stakeholders, and analysis of policy and spatial planning documents. Key innovations highlighted in this study were: ecological zoning, adaptive reuse of heritage structures, engagement with local artisans, and the implementation of renewable energy systems. The findings reveal that these interventions not only enhance environmental performance and spatial quality but also strengthen cultural identity and foster community participation. This study contributes a replicable model for heritage-based tourism revitalization in developing countries, particularly in Southeast Asia, by integrating global sustainability principles with the Balinese local philosophy of Tri Hita Karana. The proposed model offers both a theoretical contribution to the literature on urban regeneration and a practical reference for planners, architects, and policymakers